Self-Reported Cardiovascular Risk Factors Among Medical Students - Jéssica de Paula Chalup Junqueira; Lais de Souza Rodrigues; Maria Aparecida de Almeida Souza Rodrigues; Ivana Picone Borges de Aragão (Global Journal of Medical Research, 2024)
Cardiovascular diseases are the leading cause of death in the world with smoking diabetes high blood pressure dyslipidemia and a sedentary lifestyle being among the main risk factors The objective of this study was to evaluate the self knowledge about cardiovascular risk factors among medical students Methodology Observational and cross-sectional study on students from the first to the eighth semester of medicine using anonymous questionnaires containing questions about cardiovascular risk factors Results A total of 288 students paticipeted There was a higher percentage of self-declared emotional stress p 0 001 and high blood pressure p 0 007 family history of coronary heart disease CAD or stroke 0 049 in the female group The group under 20 years old practiced more physical activity p 0 023 and reported a balanced diet p 0 047 the age group between 20 and 29 years old reported a higher percentage of smoking p 0 001 and alcohol consumption p 0 048 those older than 30 years old reported a higher knowledge about family history of CAD or stroke